Study of peritoneal macrophage immunophenotype in sheep experimentally infected with Fasciola hepatica - Ruiz-Campillo, María Teresa; Molina-Hernández, Verónica; Pérez, José; Pacheco Luque, Isabel; Pérez-Caballero, Raúl; Escamilla-Sánchez, Alejandro; Martínez-Moreno, Francisco Javier; Martinez Moreno, Álvaro; Zafra, Rafael (Elsevier B.V., 2018)
During Fasciola hepatica infection, the parasite has the capability to modulate the host immune response towards a non-protector Th2 type instead of Th1. This type of immune response is closely related to the alternative activation of macrophages (M2 profile) as has been shown in vivo in murine models. In this study, an experiment was carried out in order to evaluate the expression of CD68, CD14, CD206 and iNOS in cells present in the peritoneal fluid of sheep during early stages of infection with F. hepatica (1, 3, 9 and 18 days post-infection, dpi) by immunocytochemistry. To the authors’ knowledge, this is the first report that studies the in vivo immunophenotype of macrophages from the peritoneal fluid of sheep infected with F. hepatica. Throughout the experiments the absolute number of leucocytes progressively increased, reaching its highest value at 18 dpi, mainly due to the increase of eosinophils. This immunocytochemical study had two purposes: 1) CD68 expression was assessed with Hansel counterstaining, to optimally identify peritoneal macrophages, eosinophils and lymphocytes; 2) expression of CD14, CD206 and iNOS was evaluated to identify alternative or classical pathways of macrophage activation. The results showed a significant increase in CD14 from day 3 dpi compared with the non-infected group. CD206 expression at all time-points showed a significant and dramatic increase in comparison with the uninfected group. On the other hand, iNOS expression showed little variation, and was significantly decreased at 18 dpi in comparison with the uninfected group. These results suggest that F. hepatica induces an alternative activation of peritoneal macrophages of sheep from the first day post-infection, which may facilitate parasite survival. This is the first report describing M2 activation of peritoneal macrophages in ruminants infected with F. hepatica.
Keywords: Inmunopatología; Histología; Immunopathology